Iniciación sexual y conducta preventiva en la juventud chilena - Rodríguez Garcés, Carlos (2024)
Objective: to characterize sexual initiation and sexual risk behaviors that accompany the exercise of sexuality among young people between 15 and 29 years of age in Chile. Methodology: with the results of the Tenth National Youth Survey in Chile, through an inferential statistical analysis and the application of logistic regression models, the main descriptors of sexual initiation are profiled, with emphasis on precocity, formality, and preventive behaviour. Results: according to the data, young men and women initiate sexually at early ages, however, they privilege the formality of the bond and there is a greater presence of preventive behaviour compared to the last decade. Conclusions: the importance of developing socio-educational interventions aimed at modifying risky sexual behaviors, intervening mainly on young people’s attitudes towards prevention, is emphasized.